Icariin attenuates the tumor growth by targeting miR-1-3p/TNKS2/Wnt/β-catenin signaling axis in ovarian cancer - Fu, Yanjin; Liu, Haiquan; Long, Mengsha; Song, Linliang; Meng, Zuyu; Lin, Shaozi; Zhang, Yiyao; Qin, JiaJia (Frontiers in Oncology, 2022)
Purpose: Despite various therapy advances, ovarian cancer remains an incurable disease for which survival rates have only modestly improved. Natural products are important sources of anti-cancer lead compounds. Icariin exhibited broad anti-cancer efficacy. However, the mechanism of icariin against ovarian cancer is poorly elucidated. Methods: Cell viability was detected to evaluate the effect of icariin on SKOV-3 cells. The cell cycle and apoptosis were analyzed. The transcript of SKOV-3 cells was profiled by RNA-seq. GSEA and DEGs analyses were performed to interpret gene expression data. Western blot and TOP/FOP flash assay were applied to detect Wnt/β-catenin signaling. MiRDB database and dual-luciferase reporter assay was applied to study the regulation of miR-1-3p on TNKS2. Anti-tumor efficacy of icariin was evaluated by xenograft mouse model. Immunohistochemistry was performed with antibodies against Ki67. Results: Icariin significantly suppressed the proliferation of SKOV-3 cells. Furthermore, icariin stalled cell cycle and induced apoptosis by blocking TNKS2/Wnt/β-catenin pathway through upregulating the level of miR-1-3p. Finally, icariin dramatically suppressed tumor growth in vivo. Conclusions: In this study, we demonstrated for the first time that icariin significantly attenuated the growth of ovarian tumor in xenograft mouse model. Furthermore, we systematically revealed that icariin attenuates the tumor progression by suppressing TNKS2/Wnt/β-catenin signaling via upregulating the level of miR-1-3p in ovarian cancer with transcriptome analysis.